Framework to apply risk-based approach to Identity and Access Management (IAM) to address negligent insider in the BPO - Vasquez, Merrynol Libunao (Animo Repository, 2017)
Company data became more complicated and vulnerable to the increase in the number of users. Despite policies and procedures being implemented, it is still not enough to address negligent insider in an organization. The chosen test bed for this research is the BPO Industry. It is chosen due to its high turnover rate which increases the chance that a negligent act will be committed. As an output, the research formulated a risk-based framework for Identity and Access Management (IAM) to address Negligent Insider in the BPO Industry.